Computational Investigations of the Transmembrane Italian-Mutant (E22K) 3A\(β_{11 - 40}\) in Aqueous Solution - Ngo, Son Tung (Communications in Physics, 2018)
The Amyloid beta (Aβ) oligomers are characterized as critical cytotoxic materials in Alzheimer’s disease (AD) pathogenesis. Structural details of transmembrane oligomers are inevitably necessary to design/search potential inhibitor due to treat AD. However, the experimental detections for structural modify of low-order Aβ oligomers are precluded due to the extremely dynamic fluctuation of the oligomers. In this project, the transmembrane Italian-mutant (E22K) 3Aβ11-40 (tmE22K 3Aβ11-40) was extensively investigated upon the temperature replica exchange molecular dynamics (REMD) simulations. The structural changes of the trimer when replacing the negative charged residue E22 by a positively charged residue K were monitored over simulation intervals. The oligomer size was turned to be larger and the increase of β-content was recorded. The momentous gain of intermolecular contacts with DPPC molecules implies that tmE22K 3Aβ11-40 easier self-inserts into the membrane than the WT one. Furthermore, the tighter interaction between constituting monomers was indicated implying that the E22K mutation probably enhances the Aβ fibril formation. The results are in good agreement with experiments that E22K amyloid is self-aggregate faster than the WT form. Details information of tmE22K trimer structure and kinetics probably yield the understanding of AD mechanism.